Time-varying connectedness and contagion between commodity prices and exchange rate in Sub-Saharan Africa - Richard Takyi Opoku; Anokye M. Adam; Zangina Mohammed Isshaq; Peterson Owusu Junior (Cogent Economics & Finance, 2023)
Market participants, policymakers, and practitioners might have ignored the connection between global commodities and the currency markets in sub-Saharan Africa and the potential for contagion at various time scales. We examine the degree of time-varying connectivity and contagion between commodities and the exchange rates of sub-Saharan African countries (SSA). We use the Barunik and Krehlik (BK18) spillover index on monthly data from 1990 to 2019 to illustrate the dynamic connectivity in the time and frequency domains. The BK18 captures the nonlinear, nonstationary, asymmetric, and time-dependent comovements in the relationship. Our analysis indicates that the relationship between commodity returns and exchange rates in Sub-Saharan Africa (SSA) is both time- and frequency-dependent, but stronger at higher frequencies. We observe that, among the three commodities, only crude oil is a dominant spillover propagator. The exchange rates of South Africa dominate spillover transmission among metal-producing countries, and those of Cote d'Ivoire dominate agricultural-producing countries. The dynamic results reveal significant spillovers between commodities and exchange rates during economic turmoil, indicating contagion among the markets. Since uncertainty spillover is more severe amid market upheaval, investors should use their awareness of market dynamics and fluctuations to protect their holdings from lower asset returns. Policymakers should keep a close eye on spillovers because they endanger cross-market connections.
Keywords: 330; commodity prices; contagion; exchange rate; spillovers; time-varying connectedness